2003
DOI: 10.1017/s0022336000043419
|View full text |Cite
|
Sign up to set email alerts
|

New late Cretaceous (Campanian and Maastrichtian) marine gastropods from California

Abstract: Three new genera and six new species of shallow-marine gastropods are named from Upper Cretaceous strata found mainly in California. The trochidsCidarina cretaceanew species andCidarina betanew species, the ficidBulbificopsis garzanew genus and new species, and the cancellariidMataxa aridanew species are from the Maastrichtian part of the Moreno Formation of north-central California. This is the earliest record ofCidarina, whose previous chronologic range was middle Eocene to Recent.Bulbificopsisis the first r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The material described and illustrated herein consists of both disarticulated and fully articulated skeletons collected from the Tierra Loma Shale and Garzas Sand member of the Moreno Formation, San Joaquin Valley, central California. On the basis of ammonites, gastropods and benthic foraminifers, the mosasaur‐bearing strata have been dated as late Early to early Late Maastrichtian (see Squires & Saul 2003 and references therein).…”
Section: Methodsmentioning
confidence: 99%
“…The material described and illustrated herein consists of both disarticulated and fully articulated skeletons collected from the Tierra Loma Shale and Garzas Sand member of the Moreno Formation, San Joaquin Valley, central California. On the basis of ammonites, gastropods and benthic foraminifers, the mosasaur‐bearing strata have been dated as late Early to early Late Maastrichtian (see Squires & Saul 2003 and references therein).…”
Section: Methodsmentioning
confidence: 99%
“…Current summaries of the geological details of nearly all the formations and members containing the study area Pyropsis can be found in the following papers (listed in ascending chronostratigraphic order): Hornbrook Formation, Osburger Gulch Member (Squires and Saul, 2003a); Tuna Canyon Formation, lower part (Alderson, 1988); and Redding Formation, Bear Creek Sandstone Member, Member IV, and Member V (Squires and Saul, 2003b). Comments pertaining to the occurrence of Pyropsis grahami n. sp.…”
Section: Geology and Stratigraphymentioning
confidence: 99%
“…Current summaries of the geological details of most of the formations and members containing study area opines can be found in the following papers (listed in ascending chronostratigraphic order): Frazier Siltstone, Melton Sandstone and Bear Creek Sandstone members of the Redding Formation (Squires and Saul 2003 a ); upper Baker Canyon Member of the Ladd Formation (Squires and Saul 2003 c ); Holz Shale Member of the Ladd Formation (Saul 1982); Haslam Formation (i.e. see under ‘Nanaimo Group) (Squires and Saul 2004 a ); Schulz Member of the Williams Formation (Filkorn 2007); Pigeon Point Formation (Squires and Saul 2003 b ); upper Cedar District Formation (Squires and Saul 2001; Squires and Saul 2006); Punta Baja Formation (Squires and Saul 2005); Gualala Formation (Squires and Saul 2004 b ); Point Loma Formation (Squires and Saul 2001) and ‘Garzas Sand’ and ‘Quinto Silt’ members of the Moreno Formation (Squires and Saul 2003 b ).…”
Section: Stratigraphymentioning
confidence: 99%